Модуси буття злочинності: матриця кримінолого-екзистенціального аналізу - Орлов, Ю. В.; Orlov, Y. V.; Орлов Юрій Володимирович (Вісник Кримінологічної асоціації України. - 2021. - № 1 (24). - С. 85-105, 2021)
У статті описано теоретичні та методичні передумови екзистенціального аналізу злочинності. Дана характеристика базовим положенням екзистенціалізму. Встановлена комплексна методична основа кримінолого-екзистенціального аналізу, що включає інтуїтивне пізнання, концептуалізацію, моделювання, експеріментально-екзістенціальную суб'єктивну автентичність. Сформована кримінолого-екзистенціальна матриця злочинності, в якій виділені модуси екзистенції задоволення, страждання і гібридні екзистенції з відповідними субекзістенціями.

The article is focused on theoretical, methodological grounds for the existential analysis of crime. It provides the characteristic of the basic position of existentialism. A comprehensive methodological basis of criminal and existential analysis has been established, including intuitive cognition, conceptualization, modeling, experimental and existential subjective authenticity (re-living experiment). The criminological and existential matrix of criminality has been formed. This matrix includes several modes: existences of pleasure (selfactualization, recognition, possession), suffering (physical pain, mortality, loneliness, guilt, absurdity) and hybrid existences (death, resentment, freedom, play, love, involvement, knowledge) with the corresponding subexistences.

В статье описаны теоретические и методические предпосылки экзистенциального анализа преступности. Дана характеристика базовым положениям экзистенциализма. Установлена комплексная методическая основа криминолого-экзистенциального анализа, включающая интуитивное познание, концептуализацию, моделирование, экспериментально-экзистенциальную субъективную аутентичность. Сформирована криминолого-экзистенциальная матрица преступности, в которой выделены модусы экзистенции удовольствия, страдания и гибридные экзистенции с соответствующими субэкзистенциями.
Admeasurements of crime: matrix of criminological existential analysis
Модусы бытия преступности: матрица криминолого-экзистенциального анализа
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; екзистенція; экзистенция; existence; екзистенціалізм; экзистенциализм; existentialism; екзистенціальний аналіз злочинності; экзистенциальный анализ преступности; existential analysis of crime; матриця злочинності; матрица преступности; crime matrix; модуси буття злочинності; модусы бытия преступности; modes of being a crime